Key issues in bioethics : a guide for teachers - Levinson, Ralph, 1951-; Reiss, Michael J. (Michael Jonathan), 1958- (London ; New York : RoutledgeFalmer, 2003)
Young people are talking about complex ethical issues, such as GM foods, animal rights and cloning, and bringing their views to bear in the classroom. The editors of this book set out to suggest how best teachers can become involved.
Book Cover; Title; Contents; Notes on contributors; Ethics and education; Issues and scenarios; How we reach ethical conclusions; Teaching bioethics to young people; Cloning; Interview between Professor Ian Wilmut and Ralph Levinson; Pursuing a rational analysis of cloning; Cloning? Yuk!; Clones and cloning: new reproductive futures; In vitro fertilisation; In vitro fertilisation: only for the infertile?; Surrogacy: a case study in ethics; Genetic screening; Genetic testing and screening: a mixed blessing?
Print version record.
Includes bibliographical references and index.
Ralph Levinson, Michael Reiss
eBooks on EBSCOhost
Keywords: Bioethics -- Study and teaching; Bioethics; Teaching; Domestic animals; Bioethics; Bioethical Issues; Teaching; Animals, Domestic; Biotechnology -- ethics; Bioéthique.; Enseignement; Animaux domestiques; teaching; BUSINESS & ECONOMICS -- Business Ethics; EDUCATION / General; EDUCATION / Reference; Teaching; Domestic animals; Bioethics; Bioethics -- Study and teaching